SCARLET FEVER IN PEDIATRICS: UPDATES ON DIAGNOSIS AND IMPACT OF POST-STREPTOCOCCAL COMPLICATIONS - Pedro do Valle Varela, João; Alves Ribeiro, Matheus; Aiala de Sousa Lopes, Layane; Cardoso Caus, Amanda; Dias Duarte Torres, Nicolli; Soares Gonçalves, Julia; Trajano Silveira Martins, Kailane; Carolina Fernandes Mendes, Ana; Tibério Campos Calegário, Luiza; da Glória Lopes Brito dos Reis, Thainá; Gava, Lara; Maria Moreno Lobo, Marcelle; et al. (Health and Society, 2025)
Scarlet fever is a bacterial infection caused by *Streptococcus pyogenes* which predominantly affects school-age children. Although its prevalence has decreased over the years due to the advance of antibiotics, outbreaks still occur, requiring special attention regarding early diagnosis and the prevention of post-streptococcal complications, such as rheumatic fever and glomerulonephritis. The aim of this study is to review updates in the diagnosis of scarlet fever in pediatrics, emphasizing clinical and laboratory methods, as well as assessing the impact of post-streptococcal complications on children’s health. This literature review addresses the diagnostic, epidemiological and therapeutic challenges of group A streptococcal (GAS) diseases, with a focus on scarlet fever, antimicrobial resistance, post-infectious complications and vaccine development. The analysis includes global trends, management strategies and scientific advances in dealing with these diseases. The clinical diagnosis of scarlet fever is based on the presence of fever, pharyngitis, a characteristic rash and classic signs such as strawberry tongue. Rapid tests for streptococcal antigen and oropharyngeal culture are essential laboratory tools for confirmation. Treatment with antibiotics, such as penicillin or amoxicillin, is effective in resolving the infection, but failure to start treatment early can lead to serious complications, including post-streptococcal glomerulonephritis and rheumatic fever, both of which have potential long-term impacts on cardiovascular and renal health. Therefore, scarlet fever remains a relevant concern in pediatrics due to the risk of post-streptococcal complications. Early diagnosis and appropriate management are key to preventing serious outcomes. Constant updates to clinical guidelines and access to rapid diagnostic tests are essential to improve care and reduce the impact of the disease in children.